Analysis of the textbook Task Basic language teaching "Improving Students' Reading Comprehension" Published by Cambridge University Press - Agustina Sianturi; Wisnauli Purba; Endang Putri Sinaga; Erikson Saragih (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
The purpose of carrying out this research is to provide an understanding of the students 'ability to read that is very low than it should be. In this case the students' low reading comprehension is caused by several things, namely the bad teaching and learning process makes it difficult for students to understand how to read correctly.  we use Task-based Language Teaching (TBLT) this technique is used in achieving the process of understanding and learning to read students to better and easier for students to understand. This research is a classroom action research (CAR).In this study, it was conducted in two stages, Observation and interviews were used to collect data which were then analyzed qualitatively.Students’ achievement of daily-test, the students’ self reflection in the form of rating format and the students’ achievement of post-tests were used in order to support the data collected. The results of this study indicate that TBLT can improve not only the teaching learning process but also the class 8 of SMP swasta cendramata students’ reading comprehension in recount texts.Thus, from the research on the TBLT technique, it was seen that the desire and interest of students in learning to read was increasingly diligent and began to master good reading techniques, as well as enjoying the process of learning to read.